A review of social entrepreneurship research in tourism: knowledge map, operational experiences, and roadmaps - Wang, Mingzhuo; Rasoolimanesh, S. Mostafa; Kunasekaran, Puvaneswaran (Taylor Francis, 2022)
Despite the growing social entrepreneurship (SE) literature in other disciplines, the research on tourism social entrepreneurship (TSE) is still in its infancy, and the knowledge has not been explicitly mapped. Moreover, the existing literature consists primarily of descriptive case studies of successful TSE initiatives, and few of them have reached a comprehensive conclusion on operational experiences, nor have they further reflected on the mechanisms of how these operational experiences lead to more successful TSE. Given these voids, by systematically reviewing the extant literature, this paper contributes to the literature by depicting a knowledge map, extracting 17 operational experiences, and proposing two roadmaps demonstrating the mechanisms through which these operational experiences lead to more successful TSE. Additionally, we suggest potential theories to help researchers understand the relationships in the proposed roadmaps. Lastly, this review also critically discusses the limitations and gaps of the existing literature. Particularly, this review shows that TSE researchers usually maintain a somewhat uncritical and idealistic stance on the impact of TSE because they tend to uncritically acclaim TSE as a panacea for various social problems. Based on the limitations and gaps, we also provide recommendations for future research.